DENTAL CONSIDERATIONS IN PATIENTS TAKING NEW ANTIPLATELET AND ANTICOAGULANT DRUGS - Atanaska S. Dinkova; Hristo I. Daskalov; Delian Delev (Peytchinski Publishing, 2020)
Atherosclerosis and the resulting cardiovascular and cerebrovascular diseases (myocardial infarction, coronary artery disease and stroke) are the leading cause of mortality and morbidity in the developed countries. Worldwide, over 10 million deaths per annum are caused by arterial thrombosis (ischaemic stroke, heart disease, peripheral gangrene). Leading in the treatment and prevention of thrombotic complications are the anticoagulant and antiplatelet drugs which are taken by millions of patients worldwide. A review of the literature shows that clinical trials involving dental extractions in patients taking antithrombotic drugs have been conducted for more than 50 years and are still ongoing. Recently, new antiplatelet and anticoagulant drugs: direct thrombin inhibitors, factor Xa inhibitors and a new class of oral thienopyridines (inhibitors of Glycoprotein IIb/IIIa and P2Y12 receptors) have been introduced on the market and are becoming increasingly common. The implications of these drugs during dental treatment are not yet known, and there is not enough information available within the literature on safe use during dental surgery. The purpose of the present review is to discuss the pharmacological properties of the new antiplatelet and anticoagulant drugs, their usage in the perioperative setting, and some guidance for dental practitioners performing invasive dental procedures.